Fat necrosis of transverse colon and necrotizing pancreatitis in a patient with acute lymphoblastic leukemia (ALL): cause of massive ascites and high fever - Acer, Tuğba; Malbora, Barış; Ötgün, İbrahim and Özdemir, Binnaz Handan and Coşkun, Mehmet and Özçay, Figen and Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2013)
We report a nine-year-old boy with acute lymphoblastic leukemia L3 (ALL-L3) and necrotizing pancreatitis in which necrosis was not limited to the pancreas. As our patient had a defective inflammatory process as a result of underlying malignant disease and neutropenia, the peripancreatic collection could not be limited and no pseudocyst was formed. In our patient, the unlimited inflammatory process and pancreatic secretions infiltrated the transverse mesocolon and transverse colon, leading to fat necrosis of the transverse colon, causing massive ascites and high fever. As there was no response to medical treatment, the success was achieved only by surgical resection. The infiltration of surrounding tissue and nearby organs by inflammation and fat necrosis in necrotizing pancreatitis has not been reported previously in a pediatric patient.